Field notes contributed by Stephen J. Dinsmore, summer 1988 - Dinsmore, Stephen J.et al (1988)
List of birds and locations contributed by Stephen J. Dinsmore with observers James J. Dinsmore, Marty Eby, Mark Proescholdt and others. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of summer 1988. Epson - sheet feed